2012
DOI: 10.1080/18811248.2011.636531
|View full text |Cite
|
Sign up to set email alerts
|

Studies on solubility of uranyl complexes in supercritical carbon dioxide and its controlling factors using UV-visible and17O- and19F-NMR spectroscopy

Abstract: ARTICLEStudies on solubility of uranyl complexes in supercritical carbon dioxide and its controlling factors using UV- ). The number of yl-oxygen and fluorine atoms also affected the solubility, i.e. the solubility increased in order of Cu(hfa) 2 H 2 O 5 VO(hfa) 2 H 2 O (2.5 6 10 72 M) 5 UO 2 (hfa) 2 H 2 O and in order of Cu(hfa) 2 (2.9 6 10 72 M) 5 Cr(hfa) 3 (3.0 6 10 72 M) 5 Zr(hfa) 4 (4.4 6 10 72 M). Moreover, the intermolecular interactions between CO 2 and specific atoms (yl-oxygen and fluorine) in b-dike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…onto the solution prepared by dissolving UO 2 (NO 3 ) 2 ·6H 2 O in 17 O-enriched water (H 2 17 O 30–40%; Cambridge Isotope Lab., Inc.) for 30 min . The U 17 O 2 (dfh) 2 DMSO complex was synthesized according to a previous paper . The CH 2 Cl 2 solution containing DMSO and Hdfh was dropped into the aqueous solution, dissolving U 17 O 2 (NO 3 ) 2 ·6H 2 O, followed by shaking to extract U 17 O 2 (dfh) 2 DMSO to the CH 2 Cl 2 phase.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…onto the solution prepared by dissolving UO 2 (NO 3 ) 2 ·6H 2 O in 17 O-enriched water (H 2 17 O 30–40%; Cambridge Isotope Lab., Inc.) for 30 min . The U 17 O 2 (dfh) 2 DMSO complex was synthesized according to a previous paper . The CH 2 Cl 2 solution containing DMSO and Hdfh was dropped into the aqueous solution, dissolving U 17 O 2 (NO 3 ) 2 ·6H 2 O, followed by shaking to extract U 17 O 2 (dfh) 2 DMSO to the CH 2 Cl 2 phase.…”
Section: Methodsmentioning
confidence: 99%
“…In 19 56 The U 17 O 2 (dfh) 2 DMSO complex was synthesized according to a previous paper. 57 The CH 2 Cl 2 solution containing DMSO and Hdfh was dropped into the aqueous solution, dissolving U 17 O 2 (NO 3 ) 2 •6H 2 O, followed by shaking to extract U 17 O 2 (dfh) 2 DMSO to the CH 2 Cl 2 phase. After evaporation of the CH 2 Cl 2 phase, yellow precipitates were obtained and recrystallized from CH 2 Cl 2 .…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…Hence the chelating agents used in the for-metal cations are very proper towards SFE. By altering the temperature gradient and the pressure more efficient selective and replacement over the conventional methods has been utilized for the metal ions as an ecofriendly technique [85]. SC-CO 2 extraction can provide an efficient and specific method for the separation of metal in various samples.…”
Section: Sfe In Metal Cation Extractionmentioning
confidence: 99%
“…Zanonato et al 160 have identified several uranylperoxide-carbonate complexes in solution, proposed models of their structure and determined the values of their equilibrium formation constants. Moreover, the solubility and the intermolecular interaction of several uranyl and vanadyl complexes with CO 2 have been investigated in supercritical carbon dioxide, 161 using an NMR spectrometer equipped with a high pressure cell.…”
Section: Applications Of 17 O Nmr In Chemistry and Materialsmentioning
confidence: 99%